Thermal, microstructural and textural characterisation of gelatinised corn, cassava and yam starch blends - Karam, Laura B. (2006)
The functional properties of mixtures of maize, cassava and yam starches and their relationships with microstructural characteristics were investigated. Experiments were performed following the simplex-centroid design with internal points and restrictions (upper limit) for yam starch proportion. The statistical model used (Scheffé canonical equation) was a powerful tool to predict the pastes behaviour within the limits of the experimental area. Polynomials with second level interactions were applied to obtain the surface response. Viscoelastic attributes of mixtures differed from those of individual starches. As shown by differential scanning calorimetry and microscopical observations, physical properties of the mixtures depended on the type of networks obtained. These networks varied upon yam, corn and cassava starch proportions as each one has a particular characteristic: gelatinisation temperature, granule size, swelling capacity and amylose/amylopectin ratio among others.